Concomitant Extraction of Wisdom Teeth with Bilateral Sagittal Split Osteotomy(BSSO): A Case Series (Global Journal of Medical Research, 2024)
Aim To investigate the incidence of postoperative complications including pain nerve damage swelling and infection associated with the concomitan text raction of wisdom teeth at the time of bilateral sagittal split osteotomy procedures Materials and Methods A retrospective evaluation of eight patients who underwent concomitant removal of their lower wisdomteeth eitherfullyerupted partiallyorfullyboneimpacted atthetime of their surgical procedure Bilateral sagittal split osteotomy with without LeFort 1 procedure genioplasty All patients presented to the Oral and Maxillofacial Surgery Departmentat Case Western Reserve University Postoperative complications including pain nerve dysfunction swelling and infection were examined at regular follow-up appointments after their surgical procedure Results A total of eight patients were examined for post operative complications All patients confirmed the presence of mild pain discomfort swelling in the short-term postoperatively Nerve sensation changes V3 hypoesthesia were also noted in the short and medium-term follow-ups but greatly improved in the long term Conclusion The concomitant extraction of bilateral wisdom teeth at the time of the surgical procedure with without aLeFort1orgenioplasty has no significant or permanent complications associated with the BSSO procedure